Impact of Moringa Leaf Liquid Fertilizer on P Uptake and Grain Yield of Organic Rice in Inceptisols - Dewi, Widyatmani Sih; Loveana, Okta; Rahmawati, Rani; Sudadi, Sudadi; Purwanto, Purwanto; Rachmawatie, Srie Juli; Cahyono, Ongko (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
In an effort to solve the P availability issue in Inceptisols, fermentation is one method used to enhance the quality of liqiuid organic fertilizer (LOF) made from Moringa (Moringa oleifera). The type and concentration determine the effectiveness of LOF on nutrient uptake and plant yields. This study aims to evaluate the impact of LOF types, concentrations, and their interactions on P uptake and rice grain yield in Inceptisols. The research was conducted in a greenhouse using a completely random design (CRD) with two factors. The first factor is the type of LOF, consisting of two levels, i.e., fresh and fermented Moringa extract. The second factor is the LOF concentration, with four levels (i.e., 0, 20, 40, 60, and 80 ml/l) and three replications. Data analysis using ANOVA, DMRT, and correlation. The study revealed that the interaction between LOF types and concentrations affects P uptake. The highest P uptake shown by fermented Moringa with a concentration of 60 ml/l was 20.02 mg/plant and 40 ml/l was 18.73 mg/plants., or 1.5 times higher than the control. Grain yield was not affected by type, LOF concentration, or interaction. Fermented Moringa has good potential as LOF, while the effect on grain yield needs further research.